Une activité enseignante de lecture d'album de jeunesse en CE2 : un exemple d'expertise ordinaire - Véronique Boiron (Recherches en Éducation)
The objective of this contribution is to define some of the features of the ordinary expertise displayed by a cycle 3 teacher during the reading of a children story book. The study uses two complementary methodologies: an interview during which the teacher answers questions about her practice of story book reading, and the analysis of the same teacher’s sessions devoted to this practice. My purpose is to try to understand the complexity and expertise inherent to the teacher activity. The underlying hypothesis is that the analysis of an ordinary teacher activity should lead to a better knowledge and understanding of other practices of cycle 3 children story book reading.